Dampak Media Sosial terhadap Perilaku Sosial Santri di Madrasah Aliyah Pondok Pesantren DDI Pattojo Soppeng - Ninda Purnamasari (Mathematics Education Study Program, 2025)
The advancement of technology and the accessibility of social media have introduced new challenges for santri—who generally live in an environment focused on deepening religious teachings—in maintaining social and cultural values within the DDI Pattojo Islamic Boarding School. This study aims to analyze the social behavior of santri after using social media and to identify the positive and negative impacts of social media usage on their social behavior at Madrasah Aliyah Pondok Pesantren DDI Pattojo Soppeng. This research employs a qualitative approach using a case study method. The data consists of subjective data gathered from teachers, boarding school caretakers, and santri. The research findings indicate that social media has a significant impact on the social behavior of santri, particularly in communication, interpersonal relationships, and adaptation to social values. Positive impacts of social media include broadening access to information, increasing self-confidence, fostering creativity, and shaping better behavior and mindsets among santri. With proper supervision and guidance, social media can serve as an effective tool to support the development of the santri's academic social behavior. However, negative impacts include reduced productivity, increased individualism, and the erosion of pesantren cultural values. This highlights the need for strict supervision and active mentoring by boarding school management to minimize the adverse effects of social media.